PENEGAKKAN HUKUM PIDANA BAGI PELAKU ILLEGAL LOGING DI INDONESIA DAN CARA MENANGGULANGINYA - Putri, Syafariah Nata (Cahaya Ilmu Bangsa, 2024)
Illegal Logging is an illegal logging activity or without a valid permit, this action is included in a special criminal act which includes special criminal behavior, one of which is regulated in Article 362 of the Criminal Code regarding the criminal act of theft which can be linked to this illegal logging act and is also regulated in Article 50 of Law Number 41 of 1999 concerning the prohibition of carrying out acts of destroying forests and taking and eliminating forest resources by force or without permission. This research collects and analyzes whether it is in accordance with legal norms, in this illegal logging case the application of criminal law for illegal logging perpetrators is still not fully implemented because it has not provided a deterrent effect for the perpetrators, so it is necessary to strengthen regulations regarding sanctions for perpetrators and strengthen regulations regarding good participation from the government in eradicating illegal logging and the surrounding community who have a very important role in carrying out efforts to overcome damage to the area due to illegal logging and can create a much better environmental area than before this illegal logging occurred. Strengthening these regulations requires coordination between the government and the community so that these regulations do not collide with each other and will later cause divisions. Illegal Logging merupakan kegiatan pembalakan pohon secara liar atau tanpa adanya izin yang sah, tindakan ini termasuk kedalam tindak pidana khusus yang termasuk prilaku khusus tindak pidana salah satunya diatur dalam pasal 362 KUHP mengenai tindak pidana pencurian yang dapat dikaitkan dengan tindakan illegal logging ini dan diatur pula dalam Pasal 50 Undang-Undang Nomor 41 Tahun 1999 mengenai larangan melakukan tindakan merusak hutan dan mengambil dan menghilangkan sumber daya hutan secara paksa atau tanpa adanya izin. Penelitian ini mengumpulkan dan menganalisa apakah sesuai dengan norma-norma hukum,dalam kasus illegal logging ini penerapan hukum pidana bagi pelaku illegal logging masih belum dapat dijalankan sepenuhnya dikarenakan belum memberikan efek jera bagi pelaku, maka diperlukannya penguatan peraturan mengenai sanksi bagi pelaku dan penguatan peraturan mengenai keikut sertaan baik dari pemerintah untuk ikut melakukan pemberantasan illegal logging dan masyarakat sekitaryang memiliki peran sangat penting dalam dalam melakukan upaya penanggulangan kerusakan wilayah akibat tindakan illegal logging ini dan dapat menciptakan wilayah lingkungan yang jauh lebih baik bahkan dari sebelum terjadinya tindakan illegal logging ini. Penguatan peraturan ini perlu adanya koordinasi antara pemerintah dan masyarakat agar peraturan tersebut tidak saling bertabrakan dan nantinya akan menimbulkan perpecahan.